(untitled) (PJDOL, 2023)
This article presents challenges and successes of Blended Learning experienced by students and faculty members of Directorate of Distance Education, International Islamic University Islamabad. The study has followed mixed method approach including sequential explanatory design. A survey was conducted to probe the experiences of (126) students enrolled in (FALL 2016) distance education programs, while interviews were conducted from (20) faculty members. Quantitative data were analyzed by using mean scores and percentages, while the interviews were analyzed by utilizing thematic approach